2009
DOI: 10.3748/wjg.15.748
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy with transcatheter arterial chemoembolization and percutaneous microwave coagulation for small hepatocellular carcinoma

Abstract: AIM:To assess the efficacy of combined transcatheter arterial chemoembolization (TACE) and percutaneous microwave coagulation therapy (PMCT) for small hepatocellular carcinoma (HCC). METHODS:Thirty-five patients with a total of 41 HCC nodules (≤ 3 cm in diameter) were treated with TACE followed by computed tomograghy (CT)-guided percutaneous microwave coagulation therapy (PMCT) within 1-3 wk. RESULTS:By biopsies and enhanced CT scans, complete necrosis of the tumor and 3-5 mm of the surrounding non-cancerous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Besides treating liver cancers, clinical application has been expanded to the treatment of neoplasms in other sites (Hadjicostas et al, 2006;Dib et al, 2009;Imoto et al, 2009;Pua et al, 2009;Rasekhi et al, 2009) Microwave, though less adopted at present, is a promising new modality for tumor ablation. In the past, microwave ablation was only performed in the Far East Liang et al, 2003;Liang et al, 2005;Yang et al, 2009). Encouraging therapeutic results have been obtained both for primary and metastatic liver cancers Liang et al, 2003;Liang et al, 2005;Yang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides treating liver cancers, clinical application has been expanded to the treatment of neoplasms in other sites (Hadjicostas et al, 2006;Dib et al, 2009;Imoto et al, 2009;Pua et al, 2009;Rasekhi et al, 2009) Microwave, though less adopted at present, is a promising new modality for tumor ablation. In the past, microwave ablation was only performed in the Far East Liang et al, 2003;Liang et al, 2005;Yang et al, 2009). Encouraging therapeutic results have been obtained both for primary and metastatic liver cancers Liang et al, 2003;Liang et al, 2005;Yang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, microwave ablation was only performed in the Far East Liang et al, 2003;Liang et al, 2005;Yang et al, 2009). Encouraging therapeutic results have been obtained both for primary and metastatic liver cancers Liang et al, 2003;Liang et al, 2005;Yang et al, 2009). As the potential benefits of microwave became more apparent, western investigators also began to do experimental and clinical researches recent years (Wright et al, 2003;Wright et al, 2005;Hines-Peralta et al, 2006;Hines-Peralta et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Even if some authors report smaller series of successful thermal ablation of HCC up to 7 cm in diameter, a diameter of 3-4 cm is usually accepted as the upper size limit for thermal ablation in the liver [19,20]. Other authors reported an improved complete ablation rate in thermal ablation of large HCCs after previous (chemo-)embolisation of hypervascularised HCC, resulting in a reduced heat sink effect [21,22]. According to the treatment plan of the Barcelona Liver Cancer Clinic (BCLC), lesions larger than 3 cm in diameter are intermediate or advanced stage HCCs and should be treated by transarterial chemoembolisation (TACE), systemic chemotherapy (sorafenib) or included into randomised control trials [23].…”
Section: Discussionmentioning
confidence: 94%
“…Compared with single treatment regimen, the combination therapy yielded improved results regarding complete necrosis rate, tumor growth reduction, and overall survival (8,9,18). Combined therapy might have a synergistic effect for the following reasons: microwaves produce thermal energy through dielectric heating of water molecules in the affected tissue.…”
Section: Discussionmentioning
confidence: 99%